Efektivitas Edukasi Perlindungan Anak terhadap Peningkatan Pengetahuan Orang Tua dan Guru tentang Perlindungan pada Anak - Risma, Devi; Satria, Defni; Solfiah, Yeni; N, Zulkifli; Mastuinda, Mastuinda; Pratiwi, Nanda (Unri Conference Series: Community Engagement, 2024)
This study aimed to analyze the impact of child protection education on increasing parents' and teachers' knowledge of child abuse. The problem addressed is the low level of understanding among parents and teachers regarding child protection concepts, which affects the lack of preventive actions against child abuse in family and school environments. The method used was an experimental design with a pretest-posttest approach involving 40 participants, including parents and teachers. Data were collected through questionnaires measuring participants' knowledge before and after the educational intervention. The pretest results showed that participants' knowledge was in the low category (50.13%). After the education program, the posttest results increased to 88.67%, indicating a high category. These findings suggest that education successfully enhances understanding of child protection, covering children's rights and responsibilities, community roles, and related legal procedures. The conclusion is that child protection education programs are effective in raising awareness and knowledge among parents and teachers, thus promoting a safer and more supportive environment for children's development.